(untitled) (TAMADDUN NURI JURNALI, 2025)
The article discusses the process of conquest of Central Asia by Tsarist Russia, the conquest strategy, and the political and economic situation in the local khanates.The Russian Empire carried out its conquest intentions with extreme impudence. First, Tashkent was occupied in 1865. Later, when the Governor General of Turkestan was established, he took advantage of the internal conflicts of the Khanates and won them one by one.